Opioid Use Disorder and Assessment of Patient Interactions Among Family Medicine Residents, Medical Students, and Physician Assistant Students - John G. Spangler; Catherine N. Shull; Carol A. Hildebrandt; Keli Beck Jones; Andrew L. Brewer; Mark P. Knudson; Gail S. Marion; Julienne K. Kirk (Association of American Medical Colleges, 2020)
Introduction In light of the opioid overdose epidemic in the US and the necessity of developing training to conduct difficult conversations around opioid dependence, three case-based videos were created to demonstrate providers using motivational interviewing (MI) with patients who have opioid use disorder (OUD). These vignettes displayed a primary care provider interacting with a patient seeking opioids. Methods Learners-including third-year medical and physician assistant (PA) students, and family medicine residents-viewed three videos set in a family medicine clinic and assessed clinician use of MI when interacting with patients with OUD. The patients were at different levels of acknowledging their need to change their opioid use behaviors and/or pursue treatment. Learners rated each video with an MI rating scale, and a facilitator debriefed strengths, weaknesses, and omissions regarding MI. Results Medical and PA students, and resident family physicians provided 572 ratings. Analysis of variance of mean percent incorrect was lower in residents than in all groups combined, but failed to reach statistical significance (47% + 12.0 vs 53% + 15.0, p = .43). Discussion These case-based videos with MI ratings afforded students and residents the opportunity to assess clinician use of MI techniques with patients with OUD. The MI rating scale had clinical significance (residents scored +5 points and had more training) despite lacking statistical significance. These scenarios allowed learners to recognize how to use MI when having a difficult conversation with patients who misuse opioids. We envision individual use or use for group discussion.